Components and factors of forming the content of the educational course “Housekeeping” in the system of training a teacher of technologies - Лихолат, Олена (Pedagogy of Higher and Secondary Education, 2014)
Lykholat H. V. Components and factors of forming the content of the educational course “Housekeeping” in the system of training a teacher of technologies. The article exposes theoretical and practical aspects of the process of forming the content of the educational discipline “Housekeeping” in the system of training a teacher of technologies in specialty “Fundamentals of housekeeping”. The author offers approaches towards selecting components in the educational course and substantiates the reasonable introduction of separate educational modules into the content of the program.